2005
DOI: 10.1080/01406720500256202
|View full text |Cite
|
Sign up to set email alerts
|

The online or e‐survey: a research approach for the ICT age

Abstract: DerekGlover University of LincolnBrayford PoolLincolnLN6 7TSUKderek@derekglover.co.uk E-technology as a basis of research is now being more widely considered as potential respondents can be drawn from an ever widening audience. Early work by others has shown that many respondents are keen to use the medium and that response rates are generally higher than by conventional approaches. This article summarizes the experience of researchers who have contacted all participants in a major training and development ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Eaton and Struthers (2002) reported fuller and more incisive answers to an online survey compared with a paper-based survey, where this was actually a goal of the evaluation. Glover and Bush (2005) agreed that the greatest value of the online survey was that it encouraged deeper reflection than that developed in paper-based surveys where people responded according to space available. They concluded that their online survey offered fuller answers at a relatively cheaper cost and from a wider respondent group.…”
Section: Comparison Between Paper and Online Surveysmentioning
confidence: 99%
See 3 more Smart Citations
“…Eaton and Struthers (2002) reported fuller and more incisive answers to an online survey compared with a paper-based survey, where this was actually a goal of the evaluation. Glover and Bush (2005) agreed that the greatest value of the online survey was that it encouraged deeper reflection than that developed in paper-based surveys where people responded according to space available. They concluded that their online survey offered fuller answers at a relatively cheaper cost and from a wider respondent group.…”
Section: Comparison Between Paper and Online Surveysmentioning
confidence: 99%
“…During the past decade there has been increasing use of online surveys in social and private sector market research (Spitz, Niles & Adler, 2006). Glover and Bush (2005) suggest that this may be because potential respondents can be drawn from an ever-widening audience. It is also true that online surveys are often easier and less expensive to administer than alternative survey methods, and that they have the potential to offer more flexibility and features than other survey methods (Spitz et al, 2006).…”
Section: The Advantages Of Using An Online Surveymentioning
confidence: 99%
See 2 more Smart Citations
“…The internet has become a promising alternative to collect data replacing traditional paper and pencil and face-to-face methods for scientific and market research utilizing surveys (Singh et al, 2009). Following the increased use of online methods in social research (Glover & Bush, 2005), in UX research too, online methods have become desirable given their lightweight nature, speed and relative ease-of-use (Väänänen-VainioMattila et al, 2008).…”
Section: Introductionmentioning
confidence: 98%